Cochrane Corner: how effective are interventions for reducing symptoms and signs resulting from jellyfish stings? - Jorien Laermans; Tine D'aes (International Journal of First Aid Education)
This is the third Cochrane Corner in the International Journal of First Aid Education, provided to you by Cochrane First Aid. Like any Cochrane Corner, it summarizes the findings of a Cochrane systematic review. It is meant to give first aid trainers, laypeople providing first aid, and guideline developers direct access to highly relevant first aid-related evidence tailored to them, which they might otherwise not have access to. Additionally, this Cochrane Corner is accompanied by a visual abstract that highlights the key findings. Cochrane First Aid aims to support Cochrane’s work by disseminating Cochrane evidence to a wider audience. To find out more, we refer you to Cochrane First Aid: the next step towards evidence-based first aid and the Cochrane First Aid website (firstaid.cochrane.org). This Cochrane Corner is based on a review that investigates the benefits and harms associated with interventions aimed at treating jellyfish stings in both adults and children. The updated review was developed by the Cochrane Pain, Palliative and Supportive Care Group and is published in the Cochrane Database of Systematic Reviews 2023, Issue 6, DOI: 10.1002/14651858.CD009688.pub3 (see www.cochranelibrary.com for information). Since Cochrane reviews are regularly updated as new evidence emerges and in response to feedback, the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the review. Both the Cochrane Corner and the visual abstract were checked by Dr. Richard G McGee, the corresponding author of this Cochrane review.